1995
DOI: 10.1190/1.1443850
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic waves in finely layered media

Abstract: computed synthetic seismograms for different dominant frequencies and determined in this way the ratio Aid for several different cases. For equal thicknesses of epoxy and glass, they found the ratio to be about 8, and for equal thickness sandstone and limestone, they found values between 6 and 7. From theoretical calculation, Helbig (1984)found the ratio to be about 3. The significant variation in the values found for the transitional frequency was the motivation for this study.The two velocities for a two-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 4 publications
(7 reference statements)
3
41
0
Order By: Relevance
“…Stovas and Ursin, 2007). According to Hovem (1995), for a large ratio between wavelength (λ) and thickness (d) of one cycle in the layering, the layered sector behaves as a homogeneous, effective medium (Backus, 1962). For low ratio, the alternate layers may be replaced by a thicker single layer using a time-average or ray velocity for the total depth range.…”
Section: Discussionmentioning
confidence: 99%
“…Stovas and Ursin, 2007). According to Hovem (1995), for a large ratio between wavelength (λ) and thickness (d) of one cycle in the layering, the layered sector behaves as a homogeneous, effective medium (Backus, 1962). For low ratio, the alternate layers may be replaced by a thicker single layer using a time-average or ray velocity for the total depth range.…”
Section: Discussionmentioning
confidence: 99%
“…If the wavelength is less then 10 times of the layer thickness then ray theory should be used. Other investigators have found slightly different relationships but all IRXQG D WUDQVLWLRQ DW d ≅ 5-20 (Hovem, 1995).…”
Section: Short Summary Of Ray Theory and Effective Medium Theorymentioning
confidence: 96%
“…The first case is that the wavelength is smaller than, or close to, the spatial periodicity of heterogeneity. For this case the ray theory is a proper way to describe the propagation velocity (Hovem 1995). In contrast, for the second case where the wavelength is much longer than the scale of heterogeneity, the effective medium theory is the most appropriate way to characterize wave propagation (Hovem 1995).…”
Section: Calulations Of Em Wave Velocity and Dielectric Constantmentioning
confidence: 96%